Intraventricular atypical teratoid rhabdoid tumour in an adult: a case report and literature review - Chan, Vivien; Marro, Alessandro; Chainey, Jonathan; Schmitt, Laura; Das, Sumit (Folia Neuropathologica, 2019)
We report a case of atypical teratoid/rhabdoid tumour (AT/RT) in an adult patient in the deep grey matter with extension into the lateral ventricle. To our knowledge, this is the first example of AT/RT involving the lateral ventricle in an adult. The patient presented with headache and confusion, and subsequently required emergent surgery. His postoperative course was complicated by hemorrhage into the surgical site. The location and vascularity of the tumour affected the extent of resection achieved and likely contributed to postoperative complications. We discuss radiological features of AT/RT in adults and implications for investigations and management.